The Effect Of Leadership And Motivation Factors On Performance And Quality Of Education As Teacher Intervening Variables In High Schools And Vocational Schools In Sabang City - Mohammad Iqbal; Yusniar Lubis; Sofiyan Sofiyan (Jurnal of Management and Social Sciences, 2023)
So many problems arise in the results of educational program policies implemented by the central government and even by the educational institutions themselves. So that there are pros and cons in the community who are currently pursuing this education. Therefore, it is necessary to deepen the research to determine the effect of leadership and motivational factors on the performance and quality of education as teacher intervening variables at high school and vocational high school in Sabang city. Data collection in this study used a quantitative method with a sample of 95 correspondents from SMA and SMK in Sabang City. The results of the study show that leadership has a very large influence on the progress of an educational program. In addition, motivation also has a big influence on the progress of these educational institutions. So it can be concluded that leadership and motivation have a very large influence on the progress of high school and vocational education institutions in the city of Sabang.